Two New C-benzylated Dihydrochalcone Derivatives from the Leaves of Melodorum siamensis - Prawat, Uma; Chairerk, Orapan; Phupornprasert, Unreuthai; Salae, Abdul-Wahab; Tuntiwachwuttikul, Pittaya (Planta Medica, 2013)
Two new C-benzylated dihydrochalcone derivatives, 4,2′,4′-trihydroxy-6′-methoxy-3′(2′′-hydroxybenzyl)dihydrochalcone (1) and 2′,4′-dihydroxy-4,6′-dimethoxy-3′(2′′-hydroxybenzyl)dihydrochalcone (2), along with six known flavonoid derivatives (3-8), a known dihydrochalcone dimer (9), three known aromatic esters (10–12), and one known aromatic amide (13), were isolated from the leaves of Melodorum siamensis. The structures of the compounds were elucidated by spectroscopic analysis, mainly 1D and 2D NMR techniques (1H, 13C, COSY, HMQC, and HMBC), as well as by comparison with literature data. The isolated compounds with a sufficient amount for biological assays were evaluated for their antimalarial, antimycobactirial, and cytotoxic activities. Compounds 1, 2, and 13 exhibited strong cytotoxicity against human tumor cell lines KB and NCI-H187, with IC50 values in the range of 0.66–7.16 µg/mL.
Keywords: Melodorum siamensis; Annonaceae; antimycobacterial activity; antimalarial activity; cytotoxic activity